Measuring the Efficiency of State Universities in the Aegean Region Using Data Envelopment Analysis (Third Sector Social Economic Review, 2026)
The quality of universities is of vital importance for a country’s future, not only in terms of transferring knowledge to younger generations but also in terms of supporting economic development. Data Envelopment Analysis (DEA) is a technique used to measure the relative efficiency of decision-making units (DMUs) across various sectors. In particular, it is a powerful analytical technique used to measure the efficiency of resource utilization in higher education institutions and to compare performance across universities. The aim of this study is to examine the efficiency of 15 state universities located in the Aegean Region using the SFA technique. Data obtained from the universities’ 2024 administrative activity reports were analyzed using the R programming language with input-oriented CCR and BCC models. In the analysis, the number of academic staff and the number of students were used as input variables, while the number of scientific publications and the number of graduates were used as output variables. According to the analysis results, 4 universities were found to be efficient in the CCR model, while 8 universities were found to be efficient in the BCC model. The average CCR efficiency value for the universities was calculated as 0.8762, and the average BCC efficiency value as 0.9341. The findings indicate that the inefficiency observed in some universities stems not from technical inadequacies but from scale efficiency. Additionally, target input values were calculated for the inefficient universities, highlighting necessary improvements in resource utilization. This study offers concrete policy recommendations to help universities with low efficiency use their resources more effectively and in a more balanced manner. The study’s original contribution lies in being one of the first comprehensive regional DEA analyses covering all state universities in the Aegean Region and conducted using up to date 2024 data. The findings provide policymakers and university administrators with important insights regarding improving resource allocation, enhancing scale efficiency, and developing higher education performance.
Keywords: Efficiency; Data Envelopment Analysis; University Efficiency; CCR Model; BCC Model; Efficiency Measurement; Aegean Region